Pyogenic granuloma underlying cutaneous horn in a young boy - Pragya A Nair; Rahul Krishna S Kota; Abhisheik P Pilani (Wolters Kluwer Medknow Publications, 2016)
Cutaneous horn is an elongated, keratinous projection that usually occurs over the sun-exposed areas. It is a clinical diagnosis and may overlie any benign, premalignant, or malignant conditions. Treatment includes wide surgical excision with careful histological examination to exclude a focus of malignancy. An unusual case of a pyogenic granuloma presenting as cutaneous horn on the lower lip in an 11-year-old boy is presented here.